Análise da eficiência arrecadatória do ITBI nos municípios cearenses de 2009 a 2015 - Andrade, Wanessa Gurgel Silveira de (2018)
The objective of this study is to analyze the collection of municipalities during the years of 2009 and 2015. Specifically, it is intended to make explicit the fiscal effort by the main local taxes, the Tax on Transmission of Real Estate - ITBI. To use the stochastic frontier method, which is part of the production frontier model to assess the technical efficiency of the collection of municipal entities in the state of Ceará. The results were compared with the municipalities, generally seem to be unable to turn the wealth generated into more collection. In addition, there was an inverse relationship between ITBI and FPM, with levels tending to be adjusted as transfers become representative of municipal revenues. For example, in the case of Ceará, the most distant municipalities are with the participation of the tourist sector is predominant in the local economy, from the neighboring municipalities or in the mountainous regions. It is believed to derive from the greater real estate dynamics provided by this activity.